Modal Sosial Perekat dalam Komunitas Keagamaan Jemaat Immanuel GPIB Makassar: Adhesive Social Capital in The Religious Community of The Immanuel GPIB Makassar Congregation - Charles Janneman Manuputty (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2024)
The role of adhesive social capital in ethnic diversity at GPIB Jemaat Immanuel Makassar, adhesive social capital in church services at GPIB Jemaat Immanuel Makassar and in achieving the vision and mission of the church. This research is a qualitative study conducted at the Protestant Church in Western Indonesia (GPIB) Immanuel Church Makassar. The data collection method used is through in-depth interviews conducted simultaneously with participant observation, and documentation studies to complement the results of interviews and observations. Primary data sources are church members categorised as church members and church leaders (consisting of Deacons, Elders, and Pastors). Secondary data sources are ecclesiastical documents such as the GPIB Understanding of Faith, Church Order, and the decisions of the GPIB Synod Council. Data was analysed by reducing data, presenting data, and concluding it as new findings. The results showed that the church has a distinctive social capital and has stability in binding the inner atmosphere and practical involvement of church members. The value of trust that has a "supernatural" dimension becomes a virtue that cannot be weakened by any value. This context of trust is the adhesive value that allows the church to do much in mobilising the resources of its citizens. The achievement of the vision and mission of GPIB, when viewed from the contribution of social capital, can accelerate or strengthen efforts to achieve the vision and mission. However, there are factors that interfere or hinder such as leadership attitudes that are not in line with God's will, becoming the main cause of the bias of church goals.